Role of antithrombin concentrate in treatment of hereditary antithrombin deficiency - Rodgers, George M. (Thrombosis and Haemostasis, 2009)
Antithrombin (AT) functions as a potent natural anticoagulant and serine protease inhibitor that inactivates many enzymes in the coagulation cascade. Antithrombin also possesses anti-inflammatory properties, many of which are mediated by its actions as an anticoagulant. Hereditary AT deficiency is a rare, underrecognised medical condition that is associated with inadequate endogenous anticoagulation thought to result from impaired inhibition of serine protease coagulation factors. Inherited as an autosomal dominant trait, congenital AT deficiency typically reduces functional AT levels to 40–60% of normal. As a result, individuals with hereditary AT deficiency have a ≥50% lifetime risk of venous thromboembolism (VTE). Specifically, AT deficiency is associated with a three- to seven-fold higher risk of VTE compared with other thrombophilias. Thus, maintaining adequate levels of AT during high-risk periods is an important treatment goal. Long-term anticoagulant thromboprophylaxis is not recommended in asymptomatic patients with AT deficiency because of the increased risk of haemorrhage. However, treatment guidelines recommend short-term thromboprophylaxis in high-risk clinical settings, including surgery, trauma, and management of pregnancy, labour, and delivery. The goal of treatment for patients with hereditary AT deficiency is an initial increase in AT activity to ≥120% of normal levels followed by maintenance of AT activity at ≥80% of normal levels. Plasma-derived AT, heparin, fresh frozen plasma, and human recombinant AT are treatment options for individuals with hereditary AT deficiency. The objective of this review is to discuss hereditary AT deficiency and the role of AT replacement therapy in the treatment of patients with this congenital disorder.
Keywords: Hereditary antithrombin deficiency; venous thromboembolism; antithrombin; thromboprophylaxis